Bacterial Profile of Neonatal Septicemia and Antibiotic Susceptibility Pattern of the Isolates in Tertiary Care Hospital, Dhaka, Bangladesh (Bangladesh Journal of Child Health, 2019)
Background : Neonatal septicemia (NS) is the most serious problem in special care neonatal unit (SCANU) and neonatal intensive care unit (NICU), resulting in significant morbidity and mortality. We evaluated the causative pathogens and their drug sensitivity pattern in this study, which will certainly help in the choice of specific antibiotic during treatment of septicemic neonates. The objective of this study is to isolate the causative agents of neonatal septicemia and to analyze antimicrobial susceptibility pattern of the isolates.Methodology: This prospective study was carried out from July 2001 to June 2002 in the Neonatal Unit of Bangabandhu Sheikh Mujib Medical University (BSMMU), and Special Care Baby Unit (SCABU) of Bangladesh Institute of Research and Rehabilitation of Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka. Blood samples from 100 clinically suspected NS cases were collected and processed in the microbiology laboratory of BSMMU and BIRDEM. The growths were identified by standard microbiological protocol and their antimicrobial sensitivity pattern was determined. The results were analyzed maintaining standard procedure with SPSS.Results: Of 100 cases, 31 (31%) showed positive blood culture. Gram-negative isolates were 22 (70.97%) and gram-positive 9 (29.03%). Klebsiella pneumoniae was the most common (41.9%), followed by staphylococcus aureus (29%) and E. coli (19.4%) among the isolates. All the three common isolates showed 100% resistance to ampicillin and very poor sensitivity to gentamicin. Gram-negative isolates were highly sensitive to amikacin and imipenem, where as gram-positive isolates were highly sensitive to amikacin and vancomycin.Conclusion: Neonatal septicemia was found to be 31% in this study, based on blood culture, as the gold standard investigation for diagnosis. A change in microbial spectrum and change in their antimicrobial susceptibility pattern as noticed in this study will certainly help in treating such cases with appropriate antibiotic and thereby help to decrease neonatal morbidity and mortality.Bangladesh J Child Health 2019; VOL 43 (1) :35-40